Monthly progress report of May, 2022 of BRAC University new campus development project - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the submission of monthly progress report of May, 2022 of BRACU new campus project.